The value of personal information in the e-commerce market - Toshiya Jitsuzumi; Teppei Koguchi (International Telecommunications Society (ITS), 2013)
The purpose of the analysis is to clarify the effect of personal information on switching costs in the internet shopping market. In order to shop on internet shopping sites, users must register with the site and provide information. In addition, many internet shopping sites provide the user's viewing and buying histories on the site. If a user changes to another internet shopping site, the personal information that has been registered and stored on his or her previously used site is not transferred to the new site, so the user must re-register his or her personal information. In this analysis, we empirically demonstrate the extent to which registered information, viewing histories, and buying histories drive up switching costs. This analysis revealed that when users change internet shopping sites, purchase histories or registered personal information represent switching costs of the same magnitude as traditional switching costs, such as brand attachment of familiarity with the site.
Keywords: 330